(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Bread is a convenient and economical staple worldwide. However, its susceptibility to microbial degradation led to a short shelf life. This perishable nature results in compromised food safety, increases food wastage and results in financial losses. In response to this challenge, bread processing involves the use of food additives. These are indispensable to produce breads with optimum quality. They also offer a feasible and economical solution to these pressing issues by maintaining quality, extend freshness and shelf life of bread. The review looks at a variety of food additives as well as preservatives used in bread and gives a thorough explanation of their distinct functionality and mode of action in order to investigate the possibilities of using conventional along with novel additives for optimized bread formulations and obtain better quality characteristics. The study explores their vital contributions through a comprehensive assessment of their effects on flavor, texture, colour, shelf life, and the bread baking process, considering different concentrations and pH levels. Additionally, the review addresses food safety aspects and regulations of the additives used in bread preservation. Overall, it emphasizes the indispensable role of food additives and preservatives in meeting consumer preferences along with ensuring product quality within the evolving landscape of the Indian bread industry.